Increasing Innovation In The Recycling Of Plastic Waste Based On Eco-Paving As An Effort To Realize A Green Economy In Gunung Sari Village - Imelda, Dewi Qomariah; Soimah, Nurus; Budiarti, Ika Niswatin; Lail, Jamilatul; Wulandari, Tuti; Alfiansyah, Muhammad (STKIP Singkawang, 2025)
The “Wanita Mandiri Village Waste Bank” is a community self-help group managing waste in Gunung Sari Village which has received assistance from the Faculty of Economics, North Kalimantan University since 2021 and was finally officially formed at the end of 2022. Based on the results of interviews with the head of the Wanita Mandiri Village Waste Bank group, it is necessary there is continued assistance related to increasing business capacity. Currently, public interest in saving plastic waste is very large. On the one hand, this is a good thing, but on the other hand, this is homework for waste banks to be able to re-manage plastic waste that has been collected by the community. The problem experienced by the Wanita Mandiri Village Waste Bank group is the inactivity of the waste collectors who have been collecting waste at the Gunung Sari Village Waste Bank, resulting in a buildup of plastic waste at the Wanita Mandiri Village Waste Bank. The focus of activities in this service program is to increase business capacity by making new products from plastic waste through eco-paving product training. The programs that have been implemented in this activity are: 1) procurement of smoke-friendly moist burning equipment, 2) procurement of printing equipment and paving press equipment, 3) training on innovations in recycling plastic waste products. This activity fully involves the community, especially KSM members, starting from identifying problems, planning activities to implementing activities. The Wanita Mandiri Village Waste Bank, Gunung Sari Village, has high hopes for further assistance. This activity was carried out over 2 days, namely 26-27 October 2024. In this training, participants learned to process plastic waste using certain techniques to produce Eco paving, which can be used as an environmentally friendly alternative building material. Apart from technical skills, this training also provides an understanding about sustainable waste management, helping reduce waste in the environment, and opening up business opportunities through Eco paving products that have marketable value. The technology and innovation in this activity is the procurement of smoke-friendly plastic waste incineration tools, paving molding tools and paving press toolsPeningkatan Inovasi Daur Ulang Sampah Plastik Berbasis Eco-Paving Sebagai Upaya Mewujudkan Ekonomi Hijau Di Desa Gunung SariABSTRAKBank Sampah Desa Wanita Mandiri merupakan kelompok swadaya masyarakat pengelola sampah di Desa Gunung Sari yang telah mendapat pendampingan dari Fakultas Ekonomi Universitas Kaltara sejak 2021 dan pada akhirnya resmi terbentuk sejak akhir tahun 2022. Berdasarkan hasil wawancara dengan ketua kelompok Bank Sampah Desa Wanita Mandiri, perlu adanya pendampingan lanjutan terkait dengan peningkatan kapasitas usaha. Saat ini animo masyarakat dalam menabung sampah plastik sangat besar. Satu sisi ini merupakan hal baik namun disisi lain ini merupakan PR bagi bank sampah untuk dapat mengelola kembali sampah plastik yang telah dikumpulkan oleh Masyarakat. Permasalahan yang dialami oleh kelompok Bank Sampah Desa Wanita Mandiri adalah tidak aktifnya pengepul sampah yang selama ini mengambil sampah di Bank Sampah Desa Gunung Sari sehingga terjadi penumpukan sampah plastik di Bank Sampah Wanita Mandiri. Adapun tujuan kegiatan pada program pengabdian ini adalah untuk meningkatkan kapasitas usaha dengan cara membuat produk baru berbahan baku sampah plastik melalui pelatihan produk eco-paving. Program yang telah dilaksanakan dalam kegiatan ini adalah: 1) pengadaan alat pembakaran dampah ramah asap, 2) pengadaan alat cetak dan alat press paving, 3) pelatihan inovasi daur ulang produk sampah plastik. Kegiatan ini melibatkan masyarakat khususnya anggota KSM secara penuh mulai dari indentifikasi permasalahan, perencanaan kegiatan hingga pada pelaksanaan kegiatan. Kegiatan ini dilaksanakan dalam waktu 2 hari yaitu tanggal 26-27 Oktober 2024. Dalam pelatihan ini, peserta belajar mengolah sampah plastik dengan teknik tertentu untuk menghasilkan ecopaving, yang dapat digunakan sebagai material bangunan alternatif ramah lingkungan.Selain keterampilan teknis, pelatihan ini juga memberikan pemahaman tentang pengelolaan sampah yang berkelanjutan, membantu mengurangi limbah di lingkungan, dan membuka peluang usaha melalui produk ecopaving yang bernilai jual. Teknologi dan Inovasi dalam kegiatan ini adalah pengadaan alat pembakaran sampah plastik ramah asap, alat cetakan paving dan alat press pavingKata Kunci :Bank sampah desa; Eco-paving; pengelolaan sampah plastik